Pengaruh Pemberian Pijat Bayi Terhadap Ketidak Nyamanan (Rewel) - Ismarina Ismarina; Prihayati Prihayati; Marthia Ikhlasiah; Sunengsih Sunengsih (Journal of Information Systems and Management (JISMA), 2022)
Massage as a skill has a very long history. Even massage is the oldest activity used by humans to expel fatigue and stress (fussy). At the beginning of its appearance, massage was believed to be one of the best ways to relieve fatigue, stress, muscle stiffness and aches. (Syaukani, 2015). The general purpose of this study was to explore the effect of giving infant massage to the discomfort (fussiness) of infants in PMB S, Kec. Coconut Hut Ex. Duren Sawit East Jakarta 2022. Using an experimental research plan. Experimental research is a research design that is used to find a causal relationship with research involvement. The difference in the level of influence after and before giving baby massage is (0.36). The results of the pre-posttest analysis showed the mean pretest (0.53) and posttest (0.90). In the pretest-posttest sig test, the value obtained is 0.000 <0.05. This means that there is a significant effect on giving massage to the discomfort (fussiness) in infants at PMB S. The average value of the pretest is 0.5333 and the posttest is 0.9000. Giving baby massage has an effect on overcoming discomfort in infants with a significant value of 0.000 <0.05. With this thesis, parents understand that massage that is carried out regularly and correctly can have a positive impact on infants and toddlers including babies can sleep more soundly, increase weight, reduce fussiness.